Risk factors for local atypical fibroxanthoma recurrence and progression to pleomorphic dermal sarcoma: A meta‐analysis of individualized participant data. Issue 3 (19th April 2022) - Ørholt, Mathias; Aaberg, Frederik L.; Abebe, Kiya; Walsh, S.; Roenigk, Randall K.; Venzo, Alessandro; Schmidt, Grethe; Klyver, Helle; Jensen, David H.; Herly, Mikkel; Vester‐Glowinski, Peter V.
Abstract: Background: Risk factors for local atypical fibroxanthoma (AFX) recurrence and progression to pleomorphic dermal sarcoma (PDS) have not previously been identified. Objective: To identify risk factors and provide follow‐up suggestions for local AFX recurrence and progression to PDS. Methods and Materials: A literature search was performed in the PubMed, EMBASE, and Cochrane databases. The PRISMA and MOOSE guidelines were followed. The risks of local AFX recurrence and progression to PDS were presented as Kaplan–Meier plots and risk factors were presented as hazard ratios (HRs) calculated with univariate and multivariate Cox regression. Results: Five hundred and ninety‐eight patients with AFX from 14 studies were included. Age >74 years and male sex significantly increased the risk of local recurrence (HR: 7.31 [95% confidence interval [CI]: 1.78–30.0], p < 0.01 and HR: 2.89 [95% CI: 1.04–8.01], p < 0.05, respectively). There was no difference when comparing wide local excision and Mohs' micrographic surgery ( p = 0.89). The risks of local AFX recurrence and progression to PDS after 2 years were <1%. Conclusion: A more intensive follow‐up regimen could be considered in patients >74 years old and males due to the higher risk of local AFX recurrence.